Pengelolaan Penyusunan Rencana Pelaksanaan Pembelajaran Tematik Di SDN Kleco 1 No.7 Surakarta - SUGIARTINI, Sugiartini, Prof. Dr. Sutama, M.Pd, Dr. Sabar Narimo, M.M., M.Pd (2015)
The purpose of thesis is describing organization of the thematic learning activity in design by drawing the organization of the outset component, the management of learning stages and management evaluation in organizing the thematic design in SDN Kleco I No. 7 Surakarta. The thesis is a qualitative research held in SDN Kleco I No. 7 Surakarta for about six months started from October 2014 until March 2015. The data are taken by observasing, interview, and documented. The source of data is people which is acted as an informer. The technique of collecting data uses observation, interview and documentation method. The Data analysis uses the qualitative analysis. Miles and Huberman divided them into data collection, data reduction, data display and conclusions or verification. The thesis issues the outset component of the thematic learning activity design organization in SDN Kleco I No. 7 Surakarta which consists of school identity, lesson, time allocation, main competent, based competent, aim of competent indicator, learning matters, learning ctivity, evaluation, tools, material and learning sources. The organization of learning stages consists of opening activity, main course and closed session. The evaluation organization uses authentic evaluation to have a clear description on the students progress and they objectively evaluated according to the real condition by mention the aspects of the authentic evaluation which is attitude, knowledge and skill.